ENERGY-INTEGRATED SMART TEXTILES: INTERNATIONAL TRENDS AND PROSPECTS FOR UZBEKISTAN’S RESEARCH ECOSYSTEM - Shodmonov, Jasur (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
Smart textiles—also known as electronic textiles (e-textiles)—represent a rapidly growing field in which flexible fabrics are embedded with electronic components to provide advanced functionality such as real-time sensing, data processing, and wireless communication. This study presents a modular analysis of smart textile systems by exploring five core components: sensors, microcontrollers, actuators, communication interfaces, and energy storage units. Emphasis is placed on energy autonomy through the integration of gel polymer electrolyte (GPE)-based supercapacitors, thermoelectric generators (TEGs), and piezoelectric yarns. International case studies from institutions such as MIT, KAIST, and the Chinese Academy of Sciences are used to benchmark global progress. The interdisciplinary convergence of materials science, electronics, and textile engineering is highlighted as a key enabler of innovation. The paper concludes with practical recommendations aimed at advancing national research infrastructure and accelerating the commercialization of smart wearable systems.